External Interventions and the Duration of Civil Wars - Elbadawi, Ibrahim A. (World Bank, Washington, DC, 2014)
The authors combine an empirical model of external intervention, with a theoretical model of civil war duration. Their empirical model of intervention allows them to analyze civil war duration, using "expected" rather than "actual" external intervention as an explanatory variable in the duration model. Unlike previous studies, they find that external intervention is positively associated with the duration of civil war. They distinguish partial third-party interventions that extend the length of war, from multilateral "peace" operations, which have a mandate to restore peace without taking sides - and which typically take place at war's end, or at least when both sides have agreed to a cease-fire. In a future paper, the authors will examine whether partial third-party interventions - whatever their effect on a war's duration - increase the risk of war's recurrence. If that proves true, then even if interventions reduce the length of civil war, they may do so at the cost of further destabilizing the political system, and sowing the seeds of future rebellion.